KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KUTAI BARAT - Imam Nazarudin Latif, TEODOTA BUYON, ,LCA Robin Jonathan, (EKONOMIA, 2016)
TEODOTA Buyon, Contribution To The Local Tax revenue (PAD) West Kutai. Under the guidance of (Mr. LCA.Robin Jonathan as a supervisor I and Mr. Imam Nazarudin Latif as mentors II).Based on data from the low contribution of Local Tax Revenue In Kutai Barat regency which is visible from the realization of a low in 2009 of 43.46%. Then conducted in-depth research on the Contributions of Local Taxes Against Local Revenue.The purpose of this study was to determine the Regional Tax Contributions to the Local Revenue Kutai Barat in 2010 up to 2012, and determine taxes that contribute most to the original income Kutai Barat in 2010, 2011, and 2012.Mechanical data colection in this research is the study of literature, which takes secondary data including documents and supporting data derived from Revenue Kutai Barat is calculated using the formula Contributions ie by comparing the total revenue realization of Local Taxes in a given year by the total actual revenues Revenues (PAD) in a given year multiplied by one hundred.Based on the analysis and discussion, it is known that the contribution of Local Tax Revenue Kutai Barat to the area in 2010 amounted to 20.45%, in 2011 was 24.68%, and in 2012 amounted to 21.99% means the Local Tax Contributions to the regional revenue still low. According to data that have been processed from the Administration Section at the Department of Revenue Receipts Kutai Barat, it is known that the realization of local taxes in 2010 amounted to 94.33%, in the year 2011 was 85.95% and in 2012 amounted to 82.13 %. Types of tax contributed the most in 2010 were the Tax Collection Gol.C Excavated in 2011 is Tax Tax on Acquisition of Land (BPHTB), and in 2012 is the restaurant tax.Based on these explanations, it can be concluded that the Regional Tax Kutai Barat has not contributed target. It can be seen from the achievement of the target of 2010 which was not realized 100%, and saw the same thing in 2011 and 2012 and even tended to decrease, this decrease may be caused by the increase in the target value is increased from the year 2010 until 2012.Hypothesis "advertisement tax, amusement tax, hotel tax, restaurant tax, street lighting tax, Tax Decision Excavation Gol.C, Taxes swallow's nests, Ground Water Tax and Customs Acquisition Rights to Land (BPHTB) already contribute on target against Revenue West Kutai Regency "rejected. The second hypothesis, which contributes the largest tax in 2010, 2011, and 2012 is the Tax Decision Gol.C Excavation was also rejected.